E-commerce security : - Ghosh, Anup K. (John Wiley, 1998)
This book examines the most critical security concerns for users and businesses engaging in all manner of Internet-based e-commerce. It contains six chapters. Chapter 1 gives several real-life cases of failures in one or more of these components that ultimately compromised security. Chapter 2 discusses the many risks inherent in the client-side sofware, including Web browsers, plug-ins, and active content applications such as Java applets and ActiveX controls. Chapter 3 describes several protocols now used to secure the data transaction in e-commerce applications. Chapter 4 addresses weaknesses in Web server software used to handle e-commerce transactions. Chapter 5 addresses the security of the Web server machine itself. Finally, chapter 6 provides a peek into the future of e-commerce security.